Given x = 2.

Let E (x) = x^2/3 ( x^120/ x^110) * x^-7

Then, we need to calculate E(2).

First, let us simplify the expression.

x^2/3 ( x^120 / x^110) * x^-7

Let us simplify between the brackets.

( x^120/ x^110)

We know that x^a/ x^b = x^(a-b).

==> x^120/ x^110 = x^(120-110)= x^10

==> E(x) = (x^2/3) ( x^10) * x^-7

Now we know that x^a* x^b =x^ (a+b).

==> E(x) = x^ ( 2/3 + 10 + -7)

= x^ (2/3 + 3)

= x^(11/3).

==> E(x) = x^ 11/3

Now let us substitute with x= 2.

**==> E(2) = 2^11/3 = 12.7 ( approx.)**

**Then E (x) = 12.7 when x = 2.**

If x= 2. Find x^2/3 ( x^120/ x^110) * x^-7 .

We see that f(2) is not indeterminate for x= 2.

So f(x) = x^120/x^110 could be simplified first and then we can put x = 2.

Therefore f(x) = x^120/x^110

f(x)= {x^(110+10)}/x^110 . But a^(m+n) = a^m*a^n by exponent law.

f(x) = x^110}*x^10/x^110.

f(x) = x^10.

No w put x = 2 in f(x) = x^10.

f(2) = 2^10.

f(2) = 1024.